Holt-Oram Syndrome in a family from Eastern Nepal - Paudel, Navaraj; Shrestha, Nikesh Raj; Koirala, Puru; Kafle, Ram Chandra; Jaiswal, Niraj Kumar; Thapa, Sanjeev (Journal of Advances in Internal Medicine, 2012)
Holt-Oram Syndrome is an autosomal dominant disorder with complete penetrance characterized by congenital cardiac defects and skeletal abnormalities of the upper limbs. Till now more than 300 cases have been reported showing wide spectrum of clinical signs but to the best of our knowledge, reporting of familial cases from Nepal has not been done. We found Holt-Oram syndrome in a 16 years old male patient with upper limb anomalies who was being evaluated for dyspnea and palpitation. Similar findings were later found in his two siblings. We recommend a thorough physical and cardiac evaluation for patients with limb anomalies who present with cardiac symptoms or history of recurrent pneumonias. DOI: http://dx.doi.org/10.3126/jaim.v1i2.6530 Journal of Advances in Internal Medicine 2012;01(02):70-72